Modulating mitochondria with natural extract compounds: from bench to clinical therapeutic opportunities for COPD - Qiao Wang; Ziling Zeng; Linlin Guo; Kent E. Williams; Yun Zhang; Yun Zhang; Hongmei Tang; Hang Hu; Hang Hu; Gang Qin; Kaijin Wang; Xing Wang (Frontiers in Pharmacology)
Chronic obstructive pulmonary disease (COPD) is a chronic respiratory disease that leads to death and disability worldwide, and it is caused by hereditary and environmental factors. It is characterized by chronic inflammation, emphysema, and irreversible limitation of airflow. Dual or triple therapy with a traditional approach can provide relief from COPD symptoms by reducing the frequency and severity of the outbreaks, but there are no current therapies to reverse the long-term decline in lung function. Although ICS rescue inhalers demonstrate efficacy in acute attacks, these cannot be utilized for chronic management of COPD due to adverse effects. Therefore, novel agents and therapeutic strategies are urgently needed to address this disease. It is believed that malfunctioning mitochondria are associated with COPD pathogenesis, contributing to inflammation, apoptosis, and cellular senescence. A better understanding of these mechanisms could provide novel therapeutic approaches for maintaining lung and skeletal muscle function. Many natural extract compounds show therapeutic potential for COPD and are associated with few adverse reactions. Notably, these natural compounds can improve mitochondrial function and exhibit a variety of anti-inflammatory, antioxidant, and immunomodulatory properties. In this review, we systemically summarize the pathogenic role of impaired mitochondria in COPD and the potential mechanisms by which natural extract compounds may ameliorate these impairments.